Theoretical Considerations on eGovernment in Romania and Bulgaria - Gheorghe PĂCURAR (Revista de Management Comparat International)
Electronic public administration is one of the priorities of the EU Member States. The EU membership of Romania and Bulgaria in 2007 represented the beginning of ensuring quality services to citizens in these two countries, following the same digital path as the rest of the Union. This sector of activity, which brings information and communications technology in the support of modernization, represents a challenge for both countries in terms of management of public service, but also a change of mentality for authorities and citizens. This article aims at comparing the two Member States, Romania and Bulgaria, through indicators established by the European Commission, analyzing the main trends and identifying the present status in terms of eGovernment